Case Study Of Abration Of The Musi River Bad Due To Water Waves In Coastal Prajin Village, Banyuasin I District, South Sumatera Province - Surnata; Irwan; Bambang setiawan; Purboyo; Febriansyah; Srikelana (Politeknik Pelayaran Barombong, 2021)
Abstract— Banyuasin Regency apart from geographically has a strategic location, which is located on a cross-province route, also has abundant natural resources. Geographical Location of Banyuasin Regency is located between 1.30 ° - 4.0 ° South Latitude and 104 ° 00 '- 105 ° 35' East Longitude which stretches from the central part of South Sumatra Province to the eastern part. Banyuasin Regency has an area of ​​12,431 km² and is divided into 19 sub-districts, one of which is Banyuasin I District. Banyuasin Regency has an area of ​​12,431 km² and is divided into 19 sub-districts, one of which is Banyuasin I sub-district, Banyuasin I district consists of several villages and sub-districts, Prajin village has almost the majority of its inhabitants on the banks of the Musi river, the existence of this village originated from a small population to Now it is increasing, but based on the current condition of the village, the population on the river bank is almost on average eroded up to ± 20 m2 by water waves caused by wind waves, waves caused by the speed of passing ships, and the occurrence of tidal waves. . We need to know that together. The Musi River is a river located in the province of South Sumatra, Indonesia. [1] With a length of 750 km, while the village is opposite the edge of the village prajin. The Musi River is 750 km long and is the longest river on the island of Sumatra. Since the time of the Sriwijaya Kingdom, this river has been known as the main means of transportation for the community. On the banks of the Musi River is the Boom Baru Harbor. The Musi River divides Palembang City into two areas: opposite Ilir in the north and across from the ulu in the south. The springs are sourced in the Kepahiang area, Bengkulu. This river is the mouth of nine major tributaries, namely the Komering, Rawas, Batanghari, Leko, Lakit, Kelingi, Lematang, Semangus, and Ogan rivers.